Determination of plastic limit of soil using fall cone and rolling device - Ahmad Safuan A. Rashid, author; Khairul Anuar Kassim; Ayob Katimon; Persidangan kerjuruteraan Awam (2007 : Lamgkawi : Kedah) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL